IBM eServer xSeries 450 Planning and Installation Guide - Redbooks, IBM (I B M, 2003)
The IBM eServer xSeries 450 is IBM’s new 64-bit Itanium Processor Family (IPF) Architecture server and is the first implementation of the 64-bit IBM XA-64 chipset, as part of the Enterprise X-Architecture strategy. This IBM Redbooks publication is a comprehensive resource on the technical aspects of the server, and is divided into five key subject areas:Chapter 1, Technical description introduces the server and its subsystems and describes the key features and how they work. This includes the new Extensible Firmware Interface, which provides a powerful replacement to the BIOS facility found on the IA-32 platform.Chapter 2, Positioning examines the types of applications that would be used on a server such as the x450.Chapter 3, Planning describes the considerations when planning to purchase and planning to install the x450. It covers such topics as configuration, operating system specifics, scalability, and physical site planning.Chapter 4, Installation covers the process of installing Windows Server 2003, Enterprise Edition and SuSE Linux Enterprise Server on the x450.Chapter 5, Management describes how to use the Remote Supervisor Adapter to send alerts to an IBM Director management environment.